Postcard from Margaret Ripley to her mother, 23 November 1914 (6223189193) - whatsthatpicture from... (Wikimedia Commons, 2011)
Notice image issue de Wikimedia Commons. Titre: Postcard from Margaret Ripley to her mother, 23 November 1914 (6223189193). I am uploading these postcards chronologically. I believe this was sent not more than a few days after Margaret, a nurse, had arrived in France. The front depicts Sainte Adresse, France, which must have been where she was based as she mentions walking along here. It is less than a kilometer north of the center of Le Havre. From what I can read (corrections welcome), she writes: "Sun[day]. We went to English Church this morning - the four who are at this hospital, the other 2 are having an awful time & we are all going to throw[?] it up in a week or so unless things improve. Everyone is good & kind to us here but there is No work just given out 120 Red packets sent by our [???]. Nearly all are fairly convalescent now anyway can get up mostly. Went along here for walk yesterday awe[?]-fully cold here except in wards mostly rooms of 8 beds some larger all given or lent by Havre[?] people. Love Mar"
Licence CC BY 2.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; église; transport